Cost-based constrained task scheduling in cloud environment. (2019) - Arunarani, A.R.; Manjula, D.
In the cloud environment, all the tasks are allocated and executed by using the available services in order to achieve higher performance, least total time for computation, shortest period of response time and utilisation of resources and so on. There are some serious challenges that the existing models could allocate the task to the resources without the profit maximisation scheme. The main motivation that is behind this paper is to design and develop a Cloud Manager (CM) to efficiently manage the cloud resources and also completing the jobs for the allocated resources for the given task in the cloud environment. It is implemented using a prior resource optimisation (PRO)-based allocation algorithm that takes into account execution time, transmission time and cost. The desirable feature of this paper is that the resources are allocated as per the cloud consumer request. The potency of this is presented in the cloud environment by finding the optimal and suboptimal allocation scheme of resources which maximise the profit of cloud provider and also improve the quality of scheduling solution.